Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
Answer:
Step-by-step explanation:
There's only one correct answer, and you've already responded with that answer.
Answer:
do you mean height, because then the answer would be a length of 9 and height of 6
Step-by-step explanation:
9+9=18
6+6=12
18+12=30
Answer:
2
Step-by-step explanation:
3/8+3/4+7/8
=3/8+6/8+7/8
=16/8
=2
100 + 0.50c = 1.50c <== ur equation
100 = 1.50c - 0.50c
100 = c....so he would have to sell 100 cups of coffee to break even